PENGARUH PERTUMBUHAN PERUSAHAAN DAN LEVERAGE TERHADAP PROFITABILITAS PADA PT UNILEVER INDONESIA, TBK PERIODE 2013 – 2023 - Eni Puji Astuti; Monika Rialistia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the partial and simultaneous influence of company growth and leverage on profitability at PT. Unilever Indonesia, Tbk for the period 2013-2023. The research method used is a quantitative research method. The data used is secondary data in the form of PT's financial reports. Unilever Indonesia, Tbk for the period 2013-2023. The analytical methods used are descriptive analysis, classical assumption test, correlation coefficient, coefficient of determination, simple linear regression analysis, multiple linear regression analysis and hypothesis testing with the t test and F test using SPSS version 27. The research results partially show the growth of the company in The proxy for growth has a value of tcount < ttable or -0.416 < 2.306 with a significance level of 0.688 > 0.05 so that it does not partially have a significant effect on profitability which is proxied by ROA. Leverage as proxied by DER has a value of tcount < ttable or -8.559 > 2.306 with a significance level of 0.000 < 0.05 so that v partially has a negative and significant effect on profitability as proxied by ROA. Simultaneous research results between company growth and leverage on profitability show that the value of Fcount > Ftable or 65.003 > 4.737 with a significance level of 0.000 < 0.05, simultaneously company growth and leverage have a significant effect on profitability. Meanwhile, the coefficient of determination value is 94.2%,